E-Skill Self-Efficacy and Perceived Performance in Remote Work: A Cross-Lagged Study on the Mediating Role of Technostressors - Nicoletta Massa; Valentina Sommovigo; Andrea Rubera; Chiara Consiglio (Human Behavior and Emerging Technologies)
The shift to hybrid work necessitates a deeper understanding of the personal resources that enhance employee adaptation and performance, particularly in remote settings. Grounded in social cognitive theory, this study investigates the impact of e-skill self-efficacy—employees’ confidence in managing remote work tasks, time, and balancing job demands with personal life—on perceptions of technoinvasion and techno-overload, as well as on overall and remote work performance. The study involved 899 hybrid workers from the same organization, all following a 50/50 remote and in-office schedule. Data was collected at two time points, 3 months apart. Cross-lagged model analyses revealed that higher e-skill self-efficacy was negatively related to perceptions of technoinvasion (work interfering with personal life) and techno-overload (pressure to work faster and longer due to technology). Technoinvasion was negatively associated with self-reported remote work performance, while techno-overload had a positive association. Neither technostressor significantly impacted overall performance. Moreover, technoinvasion mediated the relationship between e-skill self-efficacy and remote work performance: Hybrid workers with higher self-efficacy were less likely to experience technoinvasion, allowing them to maintain better performance in remote settings. The findings provide actionable insights for organizations seeking to optimize employee performance in increasingly digital and flexible work environments.